2021
DOI: 10.1111/jnc.15500
|View full text |Cite
|
Sign up to set email alerts
|

Kappa free light chain index as a diagnostic biomarker in multiple sclerosis: A real‐world investigation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 49 publications
3
31
1
Order By: Relevance
“…Studies using isoelectric focusing and consecutive silver staining in polyacrylamide gels for the determination of OCB reached a diagnostic sensitivity of about 99% in MS patients, which was superior to KFLC measurement [24,27,42]. However, a similar procedure for OCB determination conducted at a different laboratory site reached a diagnostic sensitivity of 89% in MS patients, indicating the dependency of conductor and rater of non-automated determination methods [43]. Studies included in this review used immunofixation, immunoblotting, or Western blotting assays for OCB determination.…”
Section: Different Determination Methods Of Ocbmentioning
confidence: 93%
See 4 more Smart Citations
“…Studies using isoelectric focusing and consecutive silver staining in polyacrylamide gels for the determination of OCB reached a diagnostic sensitivity of about 99% in MS patients, which was superior to KFLC measurement [24,27,42]. However, a similar procedure for OCB determination conducted at a different laboratory site reached a diagnostic sensitivity of 89% in MS patients, indicating the dependency of conductor and rater of non-automated determination methods [43]. Studies included in this review used immunofixation, immunoblotting, or Western blotting assays for OCB determination.…”
Section: Different Determination Methods Of Ocbmentioning
confidence: 93%
“…Over all studies, the mean prevalence of OCB positivity in MS patients was 94% (min-max: 85-100%) reflecting the importance of detection of intrathecal inflammation as a criterion for dissemination in time [24,[26][27][28][29]33,[42][43][44]47,48,55,56,[68][69][70][71][72][73][74][75]92]. Nevertheless, it has to be considered that some studies only included OCB-positive MS patients while other studies comprised a certain percentage of OCB-negative MS patients, thus leading the observed wide range of OCB prevalence [24,[26][27][28][29]33,[42][43][44]47,48,55,56,[68][69][70][71][72][73][74][75]92]. KFLC measurements, interpreted by different approaches, reached a mean diagnostic sensitivity of 94% (min-max: 72-100%) and specificity of 84% (min-max: 65-100%) in MS patients [24,…”
Section: The Value Of Kflc As a Csf Biomarker In The Diagnosis Of Msmentioning
confidence: 99%
See 3 more Smart Citations